Distribution Coefficient Calculation in Ternary Liquid-Liquid Systems - Mandagaran, Beatriz Adriana (2001)
A good description of liquid-liquid equilibrium is important to design extraction separation processes. Equilibrium data are normally needed as distribution coefficients for each individual component. In this paper we have combined activity coefficient models with Hand?s equation for tie lines to calculate distribution coefficients in ternary systems. The proposed method gives betterdistribution coefficients than those calculated using only activity coefficient models. Besides, the proposed method could be employed to extrapolate experimental information when liquid-liquid equilibrium data are few.